Perceived stigma among caregivers of mentally ill patient: A descriptive cross-sectional study - Khanal, Pratibha (Journal of Kathmandu Medical College, 2021)
Background: Stigmatising experience related to mental illness is not only confined to the patient but also experienced by their caregivers such as family members and friends. Caregivers feel down and helpless about their affiliation with stigma related to mental illness. Various research studies show that stigma related to mental illness have negative influence on caregivers which leads to concealing the status of mentally ill relatives.Objective: This study aimed to assess the level of perceived stigma among the caregivers of mentally ill patients.Methods: A descriptive cross-sectional study was conducted at Psychiatric outpatient and inpatient department of Psychiatry, Kathmandu Medical College from 30th January to August 30th 2020. Two hundred and sixteen respondents were chosen conveniently. Face to face interview was conducted using standard tool ‘Devaluation Consumers Families Scale’ to assess the perceived stigma among caregivers of mentally ill patients.Results: Perceived stigma among the caregivers of mentally ill patients was found to be medium (mean score 15.8±2.8). The caregivers perceived the community looking down on the families with mentally ill relatives (community rejection). The mean score was low (2.1±0.8) on “uncaring parents” which indicates that the respondents did not agree that parents of mentally ill patients were less responsible and caring than others.Conclusion: Caregivers of mentally ill patient perceive stigma in various forms which affects the usages of health facilities, care and support towards mentally ill relatives.Objective: This study aimed to assess the level of perceived stigma among the caregivers of mentally ill patients.Methods: A descriptive cross-sectional study was conducted at Psychiatric outpatient and inpatient department of Psychiatry, Kathmandu Medical College from 30th January to August 30th 2020. Two hundred and sixteen respondents were chosen conveniently. Face to face interview was conducted using standard tool ‘Devaluation Consumers Families Scale’ to assess the perceived stigma among caregivers of mentally ill patients. Results: Perceived stigma among the caregivers of mentally ill patients  was found to be medium (mean score 15.8±2.8). The caregivers perceived the community looking down on the families with mentally ill relatives (community rejection). The mean score was low (2.1±0.8) on “uncaring parents” which indicates that the respondents did not agree that parents of mentally ill patients were less responsible and caring than others. Conclusion: Caregivers of mentally ill patient perceive stigma in various forms which affects the usages of health facilities, care and support towards mentally ill relatives.